Information Systems Infrastructure Development - Road Ahead - Sirkemaa Seppo (Portugal, 2023)
Information systems is the basis of business activities and processes in organizations. Technology has an increasingly critical role and therefore the reliability of information systems becomes a key element in successful operations. In this article we look at information systems infrastructure development. It is the mortar and basis for any other systems and operations in modern organization. Therefore, it needs to be reliable and robust. However, as environment, needs and requirements can change rapidly, the infrastructure should also be flexible. Infrastructure development is about making incremental changes to existing infrastructure. It is rare that technology can be chosen freely, new systems become part of existing infrastructure rather than replace it. Compatibility and standards are essential elements in development of a reliable, smoothly operating infrastructure. They make interoperability of different systems and technologies possible, increasing the flexibility of infrastructure.
Proceedings of the International Conference on Applied Computing 2022 and WWW/Internet 2022